Smart Capacitive Transducer for High-Frequency Vibration Measurement - Vygantas Augutis; Gintautas Balčiūnas; Pranas Kuzas; Darius Gailius; Edita Raudienė (Sensors)
A smart capacitive transducer (SCT) for high-frequency vibration (HFV) measurements was developed, featuring self-calibration for the improvement of measurement accuracy. Measurements using this transducer are performed by positioning it over a thin (10 µm) dielectric layer on a conductive surface. This method was shown to be a non-contact vibration measurement technique for solid surfaces at frequencies over 10 kHz. Auto-calibration is performed every time the SCT is placed on the object being measured. This reduces the influence of positioning and the object’s surface properties on the measurement results. For the transducer’s auto-calibration, a predefined vibration of the measurement electrode is induced. This is achieved using a waveguide excited by a piezo element. The diameter of the developed SCT is 5 mm, with a frequency range of 10 kHz to 1 MHz, an object HFV amplitude measurement resolution of several picometers, and a repeatability error of several percent.